156 Improvement in Disease Severity in Patients With Treatment-Resistant Depression Following Treatment With Intranasal Esketamine. (15th June 2018) - Nash, Abigail; Shawi, May; Singh, Jaskaran; Daly, Ella; Copper, Kimberly; Lim, Pilar; Lane, Rosanne; Gogate, Jagadish; DiBernardo, Allitia; Hough, David; Alphs, Larry
Abstract: Background: Recognizing the importance not only of the clinician's opinion but also of the patient's experience and perspective, Sequenced Treatment Alternatives to Relieve Depression (STAR*D) utilized both clinician-reported and patient-reported outcomes in a large-scale multi-step study on antidepressant effectiveness in real-world settings. Both approaches indicate that <17% of Major Depressive Disorder (MDD) patients respond to novel oral treatments after two prior antidepressant failures. To address this low response rate and continue to investigate the use of patient-rated outcomes in clinical trials, an antidepressant with a new mechanism of action is being investigated for efficacy and safety utilizing both clinician-rated and patient-reported scales. Methods: This is a post-hoc analysis of a Janssen R&D Phase 2a clinical trial (ESKETINTRD2003). Subjects aged 20-64 withMDD without psychotic features (DSM IV) and a history of inadequate response to ≥2 antidepressants were randomized [3:1:1:1] to 1 week of twice-weekly treatment with intranasal placebo (n=33), esketamine 28 mg (n=11), 56 mg (n=11), or 84 mg (n=12). Participants taking oral antidepressants at study entry continued treatment during the study. Changes in depression severitywere measured using the Clinical Global Impression Severity (CGI-S) and the Patient Global Impression Severity (PGI-S) scales. Results: At all esketamine doses (28 mg, 56 mg, 84 mg), subjects reported a one-point mean change in PGI-S from baseline to week one compared to no change on placebo (p-values 0.005, 0.001, 0.032 respectively). Similarly, mean CGI-S scores improved for subjects receiving esketamine at all doses (p-values 0.028, 0.004, 0.049 respectively) compared to no change inplacebo subjects. These data are consistent with previously reported data based on the Montgomery Åsberg Depression Rating Scale (MADRS) and support positive correlation between patient-reported and clinician-reported outcomes. Discussion: Initial results from this Phase 2a study suggest clinically relevant improvement in depression symptoms in as early as one week when treated with twice-weekly intranasal esketamine as reported by both clinicians and patients. This work will help guide future investigations of esketamine in larger populations to provide better therapeutic options for treatment resistantMDD patients. Funding Acknowledgements: Janssen